Supervisory Teacher Coaching in K-12 Classrooms - Carmouche, Millicent; Thompson, Jelisa (Journal of the American Academy of Special Education Professionals, 2018)
Coaching has been identified as a critical support for persistent use of newly adopted practices and skills (Joyce & Showers, 1982). A systematic review of the literature was conducted to examine the literature base on supervisory coaching, an approach in which an outside expert or supervisor gives specific, positive, and corrective coaching when needed and is offered to the teacher after the completion of the observed lesson in an effort to move the recipient toward a desired level of performance (Joyce & Showers, 1981; 1982; Maeda, 2001; Simonsen, Myers, & DeLuca, 2010). Sixteen quasi-experimental and single-subject studies were identified and reviewed using quality indicators specific to quasi-experimental (Gersten et al., 2005) and single subject (Horner et al., 2005) research. Only six of the sixteen studies met all quality indicators. Mixed results were found across the studies, with six reporting improved teacher results and four reporting improved student behaviors.